1993
DOI: 10.1007/bf00167144
|View full text |Cite
|
Sign up to set email alerts
|

Xylose fermentation by Saccharomyces cerevisiae

Abstract: We have performed a comparative study of xylose utilization in Saccharomyces cerevisiae transformants expressing two key enzymes in xylose metabolism, xylose reductase (XR) and xylitol dehydrogenase (XDH), and in a prototypic xylose-utilizing yeast, Pichia stipitis. In the absence of respiration (see text), baker's yeast cells convert half of the xylose to xylitol and ethanol, whereas P. stipitis cells display rather a homofermentative conversion of xylose to ethanol. Xylitol production by baker's yeast is int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
344
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(361 citation statements)
references
References 42 publications
14
344
0
3
Order By: Relevance
“…1). However, this pathway introduces a problematic redox cofactor imbalance because XR can use both NADPH and nicotinamide adenine dinucleotide (NADH), whereas XDH uses NAD þ only, leading to high xylitol accumulation and low ethanol yields [17][18][19][20] . Xylitol formation could be reduced by providing sufficient oxygen 21 .…”
mentioning
confidence: 99%
“…1). However, this pathway introduces a problematic redox cofactor imbalance because XR can use both NADPH and nicotinamide adenine dinucleotide (NADH), whereas XDH uses NAD þ only, leading to high xylitol accumulation and low ethanol yields [17][18][19][20] . Xylitol formation could be reduced by providing sufficient oxygen 21 .…”
mentioning
confidence: 99%
“…Glyceraldehyde-3-phosphate is readily isomerized to DHAP which can then enter the lipid pathway by conversion to glycerol-3-phosphate. Previous work has shown that S. cerevisiae has insufficient levels of TAL1 to efficiently ferment xylose (Walfridsson et al, 1995;Hasunuma et al, 2011), causing a reduced capacity of flux through the PPP and a build-up of sedoheptulose-7-phosphate (Kotter and Ciriacy, 1993). Reduced oxidative PPP flux improves ethanol yield (Jeppsson et al, 2002) suggesting that having a slower carbon flux through the PPP allows time for the lipid production pathway enzymes to siphon off carbon and shunt it to lipids rather than ethanol.…”
Section: Engineering Of S Cerevisiae For Xylose Utilization and Incrmentioning
confidence: 99%
“…To meet the challenge of fermenting all the plant biomass sugars to ethanol, a number of engineered bacteria and yeasts have been produced. Pentose-fermenting S. cerevisiae strains have been generated by adding the xylose metabolic pathway from P. stipitis (Kotter and Ciriacy, 1993) and introducing the xylose isomerase gene either from a bacterium (Thermus thermophilus; Walfridsson et al, 1996) or from an anaerobic fungus (Piromyces sp. ; Kuyper et al, 2003;van Maris et al, 2007).…”
Section: Ethanol (Ch 3 Ch 2 Oh; C 2 H 6 O)mentioning
confidence: 99%